Literary History in and beyond China : Reading Text and World - Allen, Sarah, (Harvard University Asia Center, 2023)
Literary History in and beyond China: Reading Text and World explores the idea of literary history across the long span of the Chinese tradition. Although much scholarship on Chinese literature may be characterized as doing the work of literary history, there has been little theoretical engagement with received literary historical categories and assumptions, with how literary historical judgments are formed, and with what it means to do literary history in the first place. The present collection of essays addresses these questions from perspectives emerging both from within the tradition and from without, examining the anthological histories that shape the concept of a particular genre, the interpretive positions that impel our aesthetic judgments, the conceptual categories that determine how literary history is framed, and the history of literary historiography itself. As such, the essays collectively consider what it means to think through the framework of literary history, what literary history affords or omits, and what needs to be theorized in terms of literary history's constraints and possibilities. See Less